Detecting genotyping errors at Schistosoma japonicum microsatellites with pedigree information. Issue 1 (December 2015) - Gao, Yu-Meng; Lu, Da-Bing; Ding, Huan; Lamberton, Poppy
Abstract Background Schistosomiasis japonica remains a major public health problem in China. Integrating molecular analyses, such as population genetic analyses, of the parasite into the on-going surveillance programs is helpful in exploring the factors causing the persistence and/or spread ofSchistosoma japonicum . However, genotyping errors can seriously affect the results of such studies, unless accounted for in the analyses. Methods We assessed the genotyping errors (missing alleles or false alleles) of sevenS. japonicum microsatellites, using a pedigree data approach for schistosome miracidia, which were stored on Whatman FTA cards. Results Among 107 schistosome miracidia successfully genotyped, resulting in a total of 715 loci calls, a total of 31 genotyping errors were observed with 25.2 % of the miracidia having at least one error. The error rate per locus differed among loci, which ranged from 0 to 9.8 %, with the mean error rate 4.3 % over loci. With the parentage analysis software Cervus, the assignment power with these seven markers was estimated to be 89.5 % for one parent and 99.9 % for a parent pair. One locus was inferred to have a high number of null alleles and a second with a high mistyping rate. Conclusion To the authors' knowledge, this is the first time thatS. japonicum pedigrees have been used in an assessment of genotyping errors of microsatellite markers. The observed locus-specific error rate will benefit downstream epidemiological or ecological analyses ofS. japonicum with the markers.